TINJAUAN YURIDIS DASAR MUTASI PEGAWAI PETUGAS KEAMANAN (STUDI KASUS RUMAH TAHANAN NEGARA KELAS I CIPINANG PERIODE TAHUN 2022-2024) - Kartiwa; Niru Anita Sinaga (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
The importance of security and order in detention centers makes employee transfers a key human resource management tool. Previous research has not critically analyzed the legal basis for transfers, which accommodate fairness and professionalism, as well as the alignment between regulations and actual implementation. The purpose of this study is to determine the regulations governing transfers of security officers in detention centers in Indonesia and to analyze their implementation at the Class I Cipinang Detention Center for the 2022-2024 period. The research method used is normative juridical, supported by empirical evidence, with conceptual, legislative, and case-based approaches. The results show that the regulation of transfers of security officers in detention centers in Indonesia is comprehensively regulated by Law Number 20 of 2023 concerning Civil Servants (ASN), Government Regulation Number 17 of 2020, and Regulation of the Minister of Law and Human Rights No. 8 of 2021. The Class I Cipinang Detention Center for the 2022-2024 period complies with the applicable legal framework, but faces challenges such as employee resistance, a lack of replacement personnel, administrative issues, and minimal communication. Transfers have positive impacts in the form of refreshed personnel and increased security effectiveness, but can have negative consequences if not managed properly.